Nanogel enhanced antifouling antibacterial hydrogel and preparation method thereof
By adding multimorphic nanogels to the hydrogel, the problems of insufficient mechanical properties of the hydrogel dressing and excessive copper ion release rate are solved, and the combination of high moisture content, good mechanical properties and anti-fouling and anti-bacterial effects are achieved. Hydrogel ensures the safety and effectiveness of wound healing.
Patent Information
- Application Number
- CN202411380809.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
The existing hydrogel dressings have insufficient mechanical properties, poor interfacial compatibility and inability to deliver antibacterial agents stably, especially the rapid release rate of copper ions leads to toxic side effects.
By adding multi-morphological nanogels to the hydrogel, using the deformation dissipation energy of the nanogel during the stretching process, a composite hydrogel with high moisture content, good mechanical properties and anti-fouling and antibacterial characteristics was prepared. Specific methods include the preparation of crosslinking agent copper dimethacrylate, the preparation of multimorphic nanogels and the preparation of nanogel-enhanced antifouling and antibacterial hydrogels, and the preparation of different shapes by changing the ratio of crosslinking agent addition and reaction conditions. nanogels ensure the stability and slow release of copper ions.
It achieves improved mechanical properties of the hydrogel, slow release and stability of copper ions, reduces toxic side effects, improves antifouling and adhesion, and ensures the safety and effectiveness of wound healing.
Smart Images

Figure CN119192484A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a nanogel-reinforced antifouling and antibacterial hydrogel dressing and a preparation method thereof. Background Art
[0002] As the first line of defense of the human body, the skin plays an important role in resisting the invasion of harmful substances and pathogenic microorganisms. Therefore, it is extremely important to accelerate the healing process of skin wounds. Covering the wound with wound dressings can effectively build a protective barrier to resist the adverse effects of external influences and stimuli, thereby playing a positive role in promoting wound healing. With the development of society, active dressings (new wound dressings) have gradually replaced passive dressings (such as dry gauze and oil gauze). With the advancement and improvement of medical level, people's research on wound dressings has also gone from shallow to deep, and hydrogels are widely used in wound dressings due to their good biocompatibility and hydrophilicity.
[0003] However, traditional hydrogels still have some defects. For example, polyacrylamide hydrogel as a wound dressing has low swelling performance and insufficient ability to absorb and retain water; insufficient mechanical strength, easy to break, reducing the protective effect; lack of sufficient adhesion, easy to cause the dressing to slip, affecting the stability with the wound surface. In addition, polyacrylamide hydrogel also lacks antibacterial and anti-protein adhesion properties, which seriously affects its effectiveness in complex wound treatment. Existing hydrogel dressing technology generally incorporates nanoparticles (such as clay, nanosilver and carbon nanotubes), but the interface compatibility is poor, and it will reduce the water content and air permeability, limiting its long-term effectiveness and reliability in clinical application. On the other hand, because copper ions are natural antibacterial agents, copper ions are added to hydrogels in the prior art to make hydrogels have antibacterial properties to promote wound healing and prevent infection. However, the applicant found in the study that when the concentration of copper ions exceeds a certain range, it may have toxic side effects on the wound: high concentrations of copper ions can cause cell membrane damage, trigger intracellular oxidative stress reactions, produce excessive reactive oxygen species (ROS), and then damage DNA, proteins and lipids, leading to cell death; Excessive copper ions can inhibit the proliferation and migration of fibroblasts, interfere with normal collagen synthesis, and trigger local inflammatory reactions, which are not conducive to wound healing. Therefore, it is necessary to control the release rate and total amount of copper ions in the hydrogel to ensure that it remains within a safe range that has both antibacterial effects and does not adversely affect wound healing. However, most of the prior art directly loads copper ions through the hydrogel immersion method, or reduces its release rate through the interaction between copper ions and the hydrogel matrix, but the release rate of copper ions in this method is as high as 70-90% within a few hours, and there is still a technical problem that the copper ion release rate is too fast and the purpose of sustained release cannot be achieved.
[0004] Nanogels are hydrogel nanoparticles with nanometer sizes, which have the advantages of high water content, large specific surface area, and good biocompatibility. So far, no reports on nanogel-enhanced hydrogels have been found. Summary of the invention
[0005] The technical problem to be solved by the present invention is to solve the problems of insufficient mechanical properties, poor interface compatibility and inability to stably deliver antibacterial agents in existing nanocomposite hydrogel dressings. The present invention provides a nanogel-enhanced antifouling and antibacterial hydrogel and a preparation method thereof. The composite hydrogel is prepared by adding nanogel to the hydrogel, and the deformation of the nanogel during the stretching process is used to dissipate energy. The present invention prepares a composite hydrogel with high water content, good mechanical properties, antifouling and antibacterial characteristics.
[0006] The first object of the present invention is to provide a method for preparing a nanogel-enhanced antifouling and antibacterial hydrogel, comprising the following steps: (1) Preparation of cross-linking agent copper dimethacrylate: Sodium hydroxide and methacrylic acid are added to deionized water, the pH value of the solution is adjusted, and then a copper salt solution is added dropwise, the reaction is stirred, and the precipitate is collected, washed with water, and then dried to obtain a cross-linking agent, copper dimethacrylate; (2) Preparation of multi-morphology nanogels: The monomer, the cross-linking agent copper dimethacrylate and the initiator are dissolved in a solvent, and the multi-morphology nanogel is prepared by precipitation polymerization; The specific preparation method is as follows: monomer, cross-linking agent copper dimethacrylate, initiator and solvent are mixed, ultrasonically mixed, refluxed for 0.5-2 h, and after the reaction, the solvent and unreacted monomer and initiator are removed by high-speed centrifugal sedimentation, and washed repeatedly with acetonitrile, ethanol and deionized water for 3-5 times, and centrifuged to obtain high-purity, multi-morphology nanogels. Nanogels with different morphologies can be prepared by changing the addition ratio of the cross-linking agent.
[0007] (3) Preparation of nanogel-enhanced antifouling and antibacterial hydrogel: The multi-morphology nanogel in step (2) is uniformly dispersed in deionized water, and is added dropwise to an aqueous solution mixed with a hydrophilic monomer, a zwitterionic monomer, a crosslinking agent and an initiator, and subjected to high temperature or ultraviolet polymerization reaction to obtain a nanogel-enhanced antifouling and antibacterial hydrogel.
[0008] Specifically, in step (1), the molar ratio of methacrylic acid to sodium hydroxide is 1:1-1:10, preferably 1:2-1:5.
[0009] Specifically, in step (1), the pH value is 7-10.
[0010] Specifically, in step (1), the copper salt includes copper sulfate, copper chloride, and copper nitrate.
[0011] Specifically, in step (2), the monomer is methacrylic acid or acrylic acid; Specifically, in step (2), the solvent is acetonitrile; Specifically, in step (2), the initiator is a thermal initiator, including a peroxide initiator or an azo compound initiator. The azo compound initiator is preferably azobisisobutyronitrile; Specifically, in step (2), the mass ratio (crosslinking degree) of the crosslinking agent copper dimethacrylate to the monomer is 5-60%, preferably 15-35%; Specifically, in step (2), the mass ratio of the initiator to the monomer is 0.05% to 5%, preferably 0.5% to 3%; Preferably, the centrifugal speed is 6000-13000 rmp, and the centrifugal time is 3-15 min; Specifically, in step (3), the hydrophilic monomer is acrylamide; Specifically, in step (3), the zwitterionic monomer includes but is not limited to carboxylic acid betaine methyl methacrylate (CBMA), 2-methacryloyloxyethyl phosphorylcholine (MPC), polycarboxylic acid betaines, and methacryloylethyl sulfobetaine (SBMA), preferably methacryloylethyl sulfobetaine (SBMA).
[0012] Specifically, in step (3), the cross-linking agent is selected from any one of N,N-methylenebisacrylamide (MBA), 1,5-hexadiene, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate and trimethylolpropane trimethacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, glycerol trimethacrylate, glycerol triacrylate, glycerol dimethacrylate and glycerol diacrylate.
[0013] Specifically, in step (3), the initiator is a photoinitiator or a thermal initiator. The thermal initiator includes but is not limited to potassium persulfate (KPS), azobisisopropionitrile, azobisisobutyronitrile, azobisisoheptylnitrile, and dibenzoyl peroxide; the photoinitiator includes but is not limited to 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (2959), 2-hydroxy-2-methyl-1-phenyl ketone (1173), 1-hydroxy-cyclohexyl phenyl ketone (184), 4-phenylbenzophenone (PBZ), and methyl o-benzoylbenzoate (OMBB). The thermal initiator KPS is preferred.
[0014] Specifically, in step (3), the mass ratio of the zwitterionic monomer to the hydrophilic monomer is 5-50%, preferably 10-30%.
[0015] Specifically, in step (3), the ratio of the crosslinking agent to the sum of the mass of the zwitterionic monomer and the hydrophilic monomer is 0.05% to 2%, preferably 0.1% to 0.5%; Specifically, in step (3), the ratio of the initiator to the sum of the mass of the zwitterionic monomer and the hydrophilic monomer is 0.05% to 3%, preferably 0.1% to 2%; Specifically, in step (3), the ratio of the nanogel to the sum of the mass of the zwitterionic monomer and the hydrophilic monomer is 0.5-15%, preferably 1-6%.
[0016] Specifically, in step (3), the thermal initiation reaction temperature is 40°C to 90°C, and the reaction time is 0.2 to 4 h; the photoinitiation reaction time is 10 to 60 min.
[0017] The second object of the present invention is to provide an anti-nanogel-enhanced antifouling and antibacterial hydrogel prepared by the above preparation method. Beneficial Effects
[0018] Compared with the prior art, the present invention has the following significant advantages: (1) The present invention can prepare nanogels with different morphologies, such as spheres, sheets, petals, rods, etc., by changing the ingredient ratio in the precipitation polymerization reaction (mainly the crosslinking degree of the crosslinking agent), and then regulate the nanogels to enhance the overall properties of the hydrogel, such as the mechanical properties of the hydrogel, the release of copper ions, etc.
[0019] (2) The nanogel prepared by the present invention is rich in copper ions, which endows the hydrogel with natural antibacterial properties. The present invention uses copper dimethacrylate as a crosslinker for the nanogel, so that it forms a stable ionic bond with the carboxyl group on the nanogel, thereby ensuring the stability of the copper ions under storage conditions. The total amount of copper ions added is controlled by controlling the amount of nanogel added, and the nanogel is placed in a slightly acidic environment of the wound. The carboxyl group is protonated, which weakens the ionic binding force between the copper ions and the carboxyl group, promotes the dissociation of the nanogel and the release of the copper ions, and the released copper ions are slowly delivered to the wound via the hydrogel mechanism, ensuring the responsiveness, continuity and stability of the copper ion delivery, achieving slow release, and at the same time minimizing the potential toxic side effects caused by excessive copper ion concentration.
[0020] (3) In the slightly acidic environment of the wound, the nanogel will dissociate and release copper ions. The mechanical properties of the hydrogel will decrease with the release of copper ions, making it easier to replace the hydrogel dressing and avoid secondary damage to the wound.
[0021] (4) The present invention introduces zwitterions into the hydrogel matrix to reduce the adhesion to proteins and bacteria, thereby improving the antifouling property and the adhesion to the skin.
[0022] (5) There are hydrogen bonding interactions between the carboxyl groups of methacrylic acid or acrylic acid in the nanogel of the present invention and the amino groups of acrylamide and the functional groups of zwitterions in the hydrogel matrix, thereby improving the interfacial compatibility between the nanogel and the hydrogel matrix without causing phase separation. Moreover, compared with inorganic nanoparticles, the soft and flexible properties of the nanogel are more conducive to energy dissipation, thereby enhancing the mechanical strength and toughness of the hydrogel. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0024] Figure 1 This is a scanning electron microscope characterization image of the spherical nanogel prepared in Example 1 of the present invention.
[0025] Figure 2 This is a scanning electron microscope characterization image of the sheet-like nanogel prepared in Example 2 of the present invention.
[0026] Figure 3 This is a scanning electron microscope characterization image of the petal-shaped nanogel prepared in Example 3 of the present invention.
[0027] Figure 4 This is a scanning electron microscope characterization image of the rod-shaped nanogel prepared in Example 4 of the present invention.
[0028] Figure 5 It is the infrared spectrum of the rod-shaped nanogel prepared in Example 4 of the present invention.
[0029] Figure 6 It is a diagram of the swelling performance of PAM-1, PAM-2, PAM-3, and PAM-4 in the embodiments of the present invention.
[0030] Figure 7 It is a mechanical property diagram of PAM-1, PAM-2, PAM-3 and PAM-4 in the embodiments of the present invention.
[0031] Figure 8 It is a schematic diagram of the tensile force test of PAM-1 in an embodiment of the present invention.
[0032] Fig. 9 It is a comparison diagram of the contact angles of PAM-1, PAM-2, PAM-3, and PAM-4 in the embodiments of the present invention.
[0033] Fig.10 3 is the copper ion release curve of PAM-3 in the embodiment of the present invention. DETAILED DESCRIPTION
[0034] The present invention is further explained below in conjunction with specific examples, but it should be noted that the following examples are only used to explain the present invention, and cannot be used to limit the present invention, and all technical solutions that are the same or similar to the present invention are within the protection scope of the present invention. If not specifically stated, the raw materials used are commercially available products.
[0035] Example 1 A method for preparing a nanogel-enhanced antifouling and antibacterial hydrogel comprises the following steps: (1) Preparation of copper dimethacrylate crosslinker Weigh 1.6 g of sodium hydroxide and dissolve it in 10 mL of deionized water. Add 3.44 g of methacrylic acid and stir thoroughly to ensure complete reaction. Adjust the pH of the solution to 8. Add copper sulfate solution dropwise. Collect the generated blue precipitate by vacuum filtration and wash it several times with deionized water. Vacuum dry it to obtain the product: copper dimethacrylate (MAA-Cu) crosslinker.
[0036] (2) Preparation of spherical nanogels by precipitation polymerization Weigh 0.3 g of methacrylic acid, 0.008 g of azobisisobutyronitrile, copper dimethacrylate with a crosslinking degree of 18.4%, and 20 mL of acetonitrile into a 50 mL round-bottom flask, and ultrasonicate the solution for 10 min at room temperature to fully mix it and form a homogeneous solution. Place the flask in a water bath and heat it to the boiling point of the solvent, and reflux and precipitate it using a spherical condenser for 1 h. After completion, cool it to room temperature. The nanogel was washed multiple times by high-speed centrifugation (10,000 rpm, 10 min) to remove the acetonitrile solvent and unreacted monomers and initiators to obtain spherical PAA-Cu-NPS-1 nanogel. The scanning electron microscope photo of the spherical nanogel is shown in Figure 2. Figure 1 As shown, it can be seen in the figure that the nanogel is spherical.
[0037] (3) Preparation of nanogel-enhanced antifouling and antibacterial hydrogel (PAM-1) The prepared spherical PAA-Cu-NPS-1 nanogels were uniformly dispersed in deionized water at a concentration of 50 mg / mL. 1.2 g acrylamide, 0.3 g SBMA, 0.0045 g MBA, 0.0126 g KPS and 5 mL of deionized water were weighed and added to a beaker, stirred to fully dissolve, and 1 mL of nanogel solution was added thereto, stirred to mix evenly. The mixed solution was poured into a mold, placed in an electric constant temperature blast drying oven and heated at 80 °C for 30 minutes, and then taken out to obtain the nanogel-enhanced antifouling and antibacterial hydrogel (PAM-1). Example
[0038] A method for preparing a nanogel-enhanced antifouling and antibacterial hydrogel comprises the following steps: (1) copper methacrylate was prepared by the method of Example 1; (2) Preparation of sheet-like nanogels by precipitation polymerization Weigh 0.3 g of methacrylic acid, 0.008 g of azobisisobutyronitrile, copper dimethacrylate with a crosslinking degree of 26.6%, and 20 mL of acetonitrile into a 50 mL round-bottom flask, and ultrasonicate the solution for 10 min at room temperature to fully mix it and form a homogeneous solution. Place the flask in a water bath and heat it to the boiling point of the solvent, and reflux and precipitate it using a spherical condenser for 1 h. After cooling to room temperature, the prepared nanogel is obtained. The acetonitrile solvent, unreacted monomers and initiators are removed by multiple washing methods using high-speed centrifugation (12000 rpm, 6 min) to obtain sheet-like PAA-Cu-NPS-2 nanogel. The scanning electron microscope photo of the sheet-like nanogel is shown in Figure 2. Figure 2 As shown, it can be seen in the figure that the nanogel is in the form of sheets.
[0039] (3) Preparation of nanogel-enhanced antifouling and antibacterial hydrogel (PAM-2) The prepared flaky PAA-Cu-NPS-2 nanogels were uniformly dispersed in deionized water at a concentration of 50 mg / mL. 1.2 g acrylamide, 0.3 g SBMA, 0.0045 g MBA, 0.0126 g KPS and 5 mL of deionized water were weighed and added to a beaker, stirred to fully dissolve, and 1 mL of the nanogel solution was added thereto, stirred to mix evenly. The mixed solution was poured into a mold, placed in an electric constant temperature blast drying oven and heated at 80 °C for 30 minutes, and then taken out to obtain the nanogel-enhanced antifouling and antibacterial hydrogel (PAM-2). Example
[0040] A method for preparing a nanogel-enhanced antifouling and antibacterial hydrogel comprises the following steps: (1) copper dimethacrylate was prepared by the method of Example 1; (2) Preparation of petal-shaped nanogels by precipitation polymerization Weigh 0.3 g acrylic acid, 0.008 g azobisisobutyronitrile, copper dimethacrylate with a crosslinking degree of 32.3%, and 20 mL acetonitrile into a 50 mL round-bottom flask, and ultrasonicate the solution for 10 min at room temperature to fully mix it and form a homogeneous solution. Place the flask in a water bath and heat it to the boiling point of the solvent, and reflux and precipitate it using a spherical condenser for 1 h. After the end, cool it to room temperature to obtain the prepared nanogel. The nanogel was washed multiple times by high-speed centrifugation (8000 rpm, 8 min) to remove the acetonitrile solvent and unreacted monomers and initiators to obtain petal-shaped PAA-Cu-NPS-3 nanogel. The scanning electron microscope photo of the petal-shaped nanogel is shown in the figure. Figure 3 As shown, it can be seen in the figure that the nanogel is in the shape of petals.
[0041] (3) Preparation of nanogel-enhanced antifouling and antibacterial hydrogel (PAM-3) The prepared petal-shaped PAA-Cu-NPS-3 nanogels were uniformly dispersed in deionized water at a concentration of 50 mg / mL. 1.2 g acrylamide, 0.3 g SBMA, 0.0045 g MBA, 0.0126 g KPS and 5 mL of deionized water were weighed and added to a beaker, stirred to fully dissolve, and 1 mL of nanogel solution was added thereto, stirred to mix evenly. The mixed solution was poured into a mold, placed in an electric constant temperature blast drying oven and heated at 80 °C for 30 minutes, and then taken out to obtain the nanogel-enhanced antifouling and antibacterial hydrogel (PAM-3). Example
[0042] A method for preparing a nanogel-enhanced antifouling and antibacterial hydrogel comprises the following steps: (1) copper dimethacrylate was prepared by the method of Example 1; (2) Preparation of rod-shaped nanogels by precipitation polymerization Weigh 0.3 g acrylic acid, 0.007 g benzoyl peroxide, copper dimethacrylate with a crosslinking degree of 15.8%, and 20 mL acetonitrile into a 50 mL round-bottom flask, and ultrasonicate the solution for 10 min at room temperature to fully mix it and form a homogeneous solution. Place the flask in a water bath and heat it to the boiling point of the solvent, and reflux and precipitate it using a spherical condenser for 2 h. After cooling to room temperature, the prepared nanogel is obtained. The nanogel is washed multiple times by high-speed centrifugation (12000 rmp, 10 min) to remove the acetonitrile solvent and unreacted monomers and initiators, and a rod-shaped PAA-Cu-NPS-4 nanogel is obtained, and its electron microscope image is shown as follows: Figure 4 As shown in the figure, it can be clearly seen that the nanogel is in the shape of a rod. The infrared absorption spectrum of the PAA-Cu-NPS-4 nanogel is shown in the figure. Figure 5As shown in the figure, at 3455 cm -1 There is an absorption peak at 1700 cm -1 The absorption peak at 1405 cm -1 and 1507 cm -1 There are two absorption peaks at 732 cm-1, corresponding to COC stretching vibration and CH bending vibration, indicating the presence of polyacrylic acid segments; -1 There is an absorption peak at , which corresponds to the coordination bond between copper ions and ligands, indicating that PAA-Cu-NPS nanogel was successfully prepared.
[0043] (3) Preparation of nanogel-enhanced antifouling and antibacterial hydrogel (PAM-5) The prepared rod-shaped PAA-Cu-NPS-4 nanogels were uniformly dispersed in deionized water at a concentration of 50 mg / mL. 1.2 g acrylamide, 0.2 g CBMA, 0.0075 g ethylene glycol dimethacrylate, 0.01 g photoinitiator 2959 and 5 mL of deionized water were weighed and added to a beaker, stirred to fully dissolve, and 1.5 mL of nanogel solution was added thereto, stirred to mix evenly. The mixed solution was poured into a mold, placed in a UV reaction box for 20 minutes, and taken out to obtain a nanogel-enhanced antifouling and antibacterial hydrogel (PAM-5).
[0044] Comparative Example 1: Preparation of polyacrylamide hydrogel (PAM-4) Weigh 1.2 g acrylamide, 0.3 g SBMA, 0.0045 g MBA, 0.0126 g KPS and 5 mL deionized water into a beaker and stir to fully dissolve. Pour the mixed solution into the mold and heat it in an electric constant temperature blast drying oven at 80 °C for 90 minutes. After taking it out, polyacrylamide hydrogel (PAM-4) without nanogel loading was obtained.
[0045] Further experimental study of the above embodiments and comparative examples: Hydrogel swelling performance test: The swelling properties of the hydrogel were systematically evaluated using gravimetric analysis. First, the mass of the hydrogel sample in the freeze-dried state was accurately weighed and recorded as the initial weight (M 0 Secondly, the sample was placed in deionized water at room temperature to fully swell. During this period, the swollen hydrogel was taken out at predetermined time intervals, and the residual droplets on the surface were immediately removed by gently absorbing them with filter paper. Then, an electronic balance was used to accurately measure the mass of the swollen sample (M t). This process continues until the mass of the hydrogel has no significant change, indicating that the swelling equilibrium state has been achieved. To ensure the reliability of the data, each group of experiments was repeated three times and the average value was taken as the final result. The calculation formula of the swelling rate (SR) of the hydrogel is: The swelling curves of blank PAM hydrogel and PAM-1, PAM-2, and PAM-3 hydrogels loaded with PAA-Cu-NPS nanogels of different morphologies are shown in Figure 2. Figure 6 As shown in the figure, the PAM-1 hydrogel loaded with spherical PAA-Cu-NPS nanogels exhibited the best swelling performance, with a maximum swelling ratio of 185%, followed by the PAM-2 hydrogel embedded with sheet-like PAA-Cu-NPS nanogels, with a maximum swelling ratio of 174%, and the PAM-3 hydrogel loaded with petal-shaped PAA-Cu-NPS nanogels ranked third with a swelling ratio of up to 160%. This shows that the incorporation of nanogels into hydrogels can increase their water content.
[0046] Hydrogel mechanical properties test: The tensile properties of the hydrogel samples were tested using a universal material testing machine. The mechanical properties of the blank PAM hydrogel and the PAM-1, PAM-2, and PAM-3 hydrogels loaded with PAA-Cu-NPS nanogels of different morphologies were shown in Figure 2. Figure 7 The mechanical properties test results are shown in Table 1 below: Table 1 Mechanical properties of hydrogels sample Elongation at break (%) Fracture stress(kPa) Elastic modulus (kPa) Toughness(kJ / m3) PAM-1 260 35.4 20. 1 36. 1 PAM-2 158 23.4 20.6 18.3 PAM-3 140 18.9 13.7 17.6 PAM-4 123 14.5 12.5 8.8 As can be seen from the above table, the elongation, fracture stress, elastic modulus and toughness of the hydrogel loaded with nanogel are significantly improved compared with the blank hydrogel, among which the performance of the hydrogel loaded with spherical nanogel is the best.
[0047] The tensile strength of PAM-1 was further tested, and the test results are shown in the figure, where (a) is a schematic diagram of the original PAM-1 state, (b) is a twisting operation of PAM-1, (c) is a compression operation of PAM-1, (d) is a stretching operation of PAM-1, (e) is a stretching operation of PAM-1 after knotting, and (f) is a scissor piercing operation of PAM-1. It can be seen from the figure that PAM-1 can withstand external forces such as twisting, compression, and stretching, and can also be stretched and pierced by scissors after knotting. It can be seen that the mechanical properties of the hydrogel are significantly enhanced by loading PAA-Cu-NPS nanogel into the blank PAM hydrogel.
[0048] Hydrogel contact angle test: The contact angles of the surfaces of the hydrogels in Examples 1-3 and Comparative Examples were measured using a DSA 25 contact angle meter. The test results are shown in Table 2 below: Table 2 Contact angles of different PAM hydrogels sample Contact angle (°) PAM-1 37.65±0.06 PAM-2 45.50±0.05 PAM-3 46.15±0.04 PAM-4 56.75±0.04 Comparison of contact angles of blank PAM-4 hydrogel and PAM-1, PAM-2, and PAM-3 hydrogels loaded with spherical, plate-shaped, and petal-shaped PAA-Cu-NPS nanogels, respectively. Fig. 9 As shown in the figure, (a), (b), (c), and (d) are PAM-1, PAM-2, PAM-3, and PAM-4, respectively. When θ<90°, the liquid is easier to wet the solid. The smaller the angle, the better the wettability. From Table 2 and Fig. 9 It can be seen that the incorporation of PAA-Cu-NPS nanogel significantly improved the hydrophilicity of the PAM hydrogel surface. Among them, the PAM hydrogel incorporating spherical PAA-Cu-NPS nanogel has the best hydrophilicity, followed by the PAM hydrogel incorporating flaky PAA-Cu-NPS nanogel, and finally the PAM hydrogel incorporating petal-shaped PAA-Cu-NPS nanogel.
[0049] Copper ion release test: The hydrogel sample PAM-3 was placed in a centrifuge tube filled with PBS (10 mL, pH 6.5) and placed in a 37°C constant temperature shaker for shaking. At regular intervals, 1 mL of release medium was drawn and the same volume of fresh medium was added. Inductively coupled plasma mass spectrometry (ICP-MS) was used to quantify the copper ions in the release medium and draw a release curve. Fig.10 As shown in the figure, in a weakly acidic environment, the nanogel slowly dissociates and the copper ions are slowly released. The copper ion release rate is 11.5% after 24 hours, 29.6% after 48 hours, and 50.4% after 72 hours. It can be seen that the hydrogel of the present invention can achieve slow release of copper ions, solving the technical problem of too fast copper ion release rate in the prior art.
[0050] Antibacterial performance test: Different hydrogel samples (PAM-4, PAM-1, PAM-5) were co-cultured with Staphylococcus aureus for 24 hours, and the OD values of the bacterial solution were measured at a wavelength of 600 nm on an ELISA instrument. The antibacterial properties of the hydrogel were determined by comparing the OD values. Three groups were tested in parallel each time, and the test results are shown in Table 3 below: Table 3 OD value results of different hydrogel samples
[0051] As can be seen from the above table, the OD value of the hydrogel group loaded with copper-containing nanogel is much smaller than the OD value of the blank hydrogel, indicating that the hydrogel group loaded with copper-containing nanogel has a significant antibacterial effect on Staphylococcus aureus.
[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. All components not specified in this embodiment can be implemented using existing technologies.
Claims
1. A method for preparing a nanogel-enhanced antifouling and antibacterial hydrogel, characterized in that: The following steps are involved: (1) Preparation of cross-linking agent copper dimethacrylate: Sodium hydroxide and methacrylic acid are added to deionized water, the pH value of the solution is adjusted, and then a copper salt solution is added dropwise, the reaction is stirred, and the precipitate is collected, washed with water, and then dried to obtain a cross-linking agent, copper dimethacrylate; (2) Preparation of multi-morphology nanogels: The monomer, the cross-linking agent copper dimethacrylate and the initiator are dissolved in a solvent, and the multi-morphology nanogel is prepared by precipitation polymerization; (3) Preparation of nanogel-enhanced antifouling and antibacterial hydrogel: The multi-morphology nanogel in step (2) is uniformly dispersed in deionized water, and is added dropwise to an aqueous solution mixed with a hydrophilic monomer, a zwitterionic monomer, a crosslinking agent and an initiator, and subjected to high temperature or ultraviolet polymerization reaction to obtain a nanogel-enhanced antifouling and antibacterial hydrogel.
2. The method for preparing the nanogel-enhanced antifouling and antibacterial hydrogel according to claim 1, characterized in that: In the step (1), the molar ratio of methacrylic acid to sodium hydroxide is 1:1-1:10, preferably 1:2-1:5; the pH value is 7-10; and the copper salt includes copper sulfate, copper chloride, and copper nitrate.
3. The method for preparing the nanogel-enhanced antifouling and antibacterial hydrogel according to claim 1, characterized in that: The specific preparation method of step (2) is as follows: monomers, cross-linking agent copper dimethacrylate, initiator and solvent are mixed, ultrasonically mixed, refluxed for 0.5 to 2 hours, and after the reaction is completed, the solvent and unreacted monomers and initiators are removed by high-speed centrifugal sedimentation, and the mixture is repeatedly washed with acetonitrile, ethanol and deionized water for 3 to 5 times, and centrifuged to obtain a high-purity, multi-morphology nanogel.
4. The method for preparing the nanogel-enhanced antifouling and antibacterial hydrogel according to claim 1 or 3, characterized in that: In the step (2), the monomer is methacrylic acid or acrylic acid; the solvent is acetonitrile; The initiator is a thermal initiator, including a peroxide initiator or an azo compound initiator, preferably an azo compound initiator azobisisobutyronitrile; The centrifugal speed is 6000~13000 rmp and the centrifugal time is 3~15 min.
5. The method for preparing the nanogel-enhanced antifouling and antibacterial hydrogel according to claim 1, characterized in that: In the step (2), the mass ratio of the cross-linking agent copper dimethacrylate to the monomer is 5-60%, preferably 15-35%; The mass ratio of the initiator to the monomer is 0.05% to 5%, preferably 0.5% to 3%.
6. The method for preparing the nanogel-enhanced antifouling and antibacterial hydrogel according to claim 1, characterized in that: In the step (3), the hydrophilic monomer is acrylamide; The zwitterionic monomers include but are not limited to carboxylic acid betaine methyl methacrylate (CBMA), 2-methacryloyloxyethyl phosphorylcholine (MPC), polycarboxylic acid betaines, methacryloylethyl sulfobetaine (SBMA), preferably methacryloylethyl sulfobetaine (SBMA); The cross-linking agent includes but is not limited to N,N methylenebisacrylamide (MBA), 1,5-hexadiene, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate and trimethylolpropane trimethacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, glycerol trimethacrylate, glycerol triacrylate, glycerol dimethacrylate, glycerol diacrylate; The initiator is a photoinitiator or a thermal initiator. The thermal initiator includes but is not limited to potassium persulfate (KPS), azobisisopropionitrile, azobisisobutyronitrile, azobisisoheptylnitrile, and dibenzoyl peroxide; the photoinitiator includes but is not limited to 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (2959), 2-hydroxy-2-methyl-1-phenyl ketone (1173), 1-hydroxy-cyclohexyl phenyl ketone (184), 4-phenylbenzophenone (PBZ), and methyl o-benzoylbenzoate (OMBB). The thermal initiator KPS is preferred.
7. The method for preparing the nanogel-enhanced antifouling and antibacterial hydrogel according to claim 1 or 6, characterized in that: In the step (3), the mass ratio of the zwitterionic monomer to the hydrophilic monomer is 5-50%, preferably 10-30%; The ratio of the crosslinking agent to the sum of the mass of the zwitterionic monomer and the hydrophilic monomer is 0.05% to 2%; The ratio of the initiator to the sum of the mass of the zwitterionic monomer and the hydrophilic monomer is 0.05% to 3%; The ratio of the nanogel to the sum of the mass of the zwitterionic monomer and the hydrophilic monomer is 0.5-15%.
8. The method for preparing the nanogel-enhanced antifouling and antibacterial hydrogel according to claim 7, characterized in that: The mass ratio of the zwitterionic monomer to the hydrophilic monomer is 10-30%; The ratio of the crosslinking agent to the sum of the mass of the zwitterionic monomer and the hydrophilic monomer is 0.1-0.5%; The ratio of the initiator to the sum of the mass of the zwitterionic monomer and the hydrophilic monomer is 0.1-2%; The nanogel accounts for 1-6% of the total mass of the zwitterionic monomer and the hydrophilic monomer.
9. The method for preparing the nanogel-enhanced antifouling and antibacterial hydrogel according to claim 1, characterized in that: In step (3), the thermal initiation reaction temperature is 60°C to 90°C, and the reaction time is 0.2 to 6 h; the photoinitiation reaction time is 5 to 60 min.
10. The nanogel-reinforced antifouling and antibacterial hydrogel prepared according to any one of claims 1 to 9.
Citation Information
Cited By
Photoresponsive drug gel carrier and preparation method thereof
CN120585728A